Combining Nanofocused X-Rays with Electrical Measurements at the NanoMAX Beamline - Lert Chayanun; Susanna Hammarberg; Hanna Dierks; Gaute Otnes; Alexander Björling; Magnus T Borgström; Jesper Wallentin (Crystals, 2019)
The advent of nanofocused X-ray beams has allowed the study of single nanocrystals and complete nanoscale devices in a nondestructive manner, using techniques such as scanning transmission X-ray microscopy (STXM), X-ray fluorescence (XRF) and X-ray diffraction (XRD). Further insight into semiconductor devices can be achieved by combining these techniques with simultaneous electrical measurements. Here, we present a system for electrical biasing and current measurement of single nanostructure devices, which has been developed for the NanoMAX beamline at the fourth-generation synchrotron, MAX IV, Sweden. The system was tested on single InP nanowire devices. The mechanical stability was sufficient to collect scanning XRD and XRF maps with a 50 nm diameter focus. The dark noise of the current measurement system was about 3 fA, which allowed fly scan measurements of X-ray beam induced current (XBIC) in single nanowire devices.